The deterioration of concrete in wastewater treatment plants - Sarray, Anmar Abdulwahid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Loss of serviceability over time is the simplest definition of deterioration. Concrete deterioration can be a result of the interaction of several factors that affect the structure of concrete in terms of durability. Wastewater treatment plant concretes must resist all the natural factors and operational impacts without the need of major maintenance and repair. For this reason high quality and durable concretes should be designed. The compressive strength, durability of concrete and the corrosion in reinforcement steel bars; might be affected due to the harmless effect of acidic wastewater with the passing time. This thesis states the harmful effects of the wastewater on concrete durability and the properties of concrete which is suitable for wastewater treatment plant purposes were studied. The most recently built wastewater plants Gazimağusa plant, Baquba-Iraq plant and EMU campus plant have been investigated. In addition, some laboratory experiments have been performed for EMU campus wastewater treatment plant. At the end of this study it can be concluded that, high durable concrete should be produced in order to prevent its deterioration either at early stages or to extend its lifetime service. Keywords: Wastewater Treatment Plant, Corrosion, Permeability, Microorganism, Durable Concrete. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Hasar, en basit bağlamda herhangi bir yapı elemanının zaman aşımına bağlı olarak işlevini yitirmesi olarak tanımlanabilir. Betonda oluşan hasar, birçok faktöre bağlı olarak betonun yapısını dayanıklılık açısından etkilemektedir. Arıtma tesislerinde kullanılacak olan betonun, bütün doğal faktörlere ve çalışma anında oluşan çarpmaların şiddetine çok fazla bakım ve tamirat gerektirmeden direnç gösterebilmesi gerekmektedir. Bu sebeple, arıtma tesisi beton tasarımı yapılırken yüksek kalite ve dayanıklılık ön planda tutulmalıdır. Beton basınç dayanımı, dayanıklılığı ve de beton içerisindeki çelik donatıların bütünlüğü geçen zamanla birlikte pis su atıklarındaki asitin etkisi altında zarara uğrayabilirler. Bu tez çalışmasında; pis su atıklarının betonun dayanıklılığı üzerindeki zararlı etkileri ve de bu amaç için kullanılacak betonda olması gereken özelikler araştırılmıştır. Yakın geçmişte inşaa edilmiş olan Gazimağusa ve Baquba-Irak arıtma tesisleri ile Doğu Akdeniz Üniversitesi (DAÜ) arıtma tesisi incelenmiştir. Buna ek olarak, DAÜ kampüsü arıtma tesisinde bazı laboratuvar deneyleri de gerçekleştirilmiştir. Bu çalışmanın neticesinde; arıtma tesisi betonunun hem erken yaşlarda hem de uzun süre içerisinde hasara uğramaması için yüksek dayanıklılıkta üretilmesi getektiği sonucuna varılmıştır. Anahtar Kelimeler: Arıtma Tesisi, Beton, Mikroorganizma, Geçirimlilik, Dayanıklılık, Paslanma.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2013. Supervisor: Assist. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering; Wastewater Treatment Plant, Corrosion, Permeability, Microorganism, Durable Concrete